2015
DOI: 10.1155/2015/842143
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Stereoscopic Vision, Visual Perception, and Microstructure Changes of Corpus Callosum and Occipital White Matter in the 4-Year-Old Very Low Birth Weight Children

Abstract: Aim. To assess the relationship between stereoscopic vision, visual perception, and microstructure of the corpus callosum (CC) and occipital white matter, 61 children born with a mean birth weight of 1024 g (SD 270 g) were subjected to detailed ophthalmologic evaluation, Developmental Test of Visual Perception (DTVP-3), and diffusion tensor imaging (DTI) at the age of 4. Results. Abnormal stereoscopic vision was detected in 16 children. Children with abnormal stereoscopic vision had smaller CC (CC length: 53 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Of 57 patients included, 36 (63.2%) were male and 21 (36.8%) were female. The median age was 13 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) months and the median followup period was 11 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) were esotropic and 16 (28.1%) was exotropic. In the anterior segment examinations of the patients; 2 patients (3.5%) had ptosis, 1 (1.7%) had megalo-cornea and blue sclera, and 1 (1.7%) had shallow orbit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 57 patients included, 36 (63.2%) were male and 21 (36.8%) were female. The median age was 13 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) months and the median followup period was 11 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) were esotropic and 16 (28.1%) was exotropic. In the anterior segment examinations of the patients; 2 patients (3.5%) had ptosis, 1 (1.7%) had megalo-cornea and blue sclera, and 1 (1.7%) had shallow orbit.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it is thought to have a complex relationship between the parts of the corpus callosum and visual function. Kwinta et al 14 found that there is a correlation between the function of rostrum, genu and body of the corpus callosum and stereoscopic vision. Dougherty et al 15 showed projections between the occipital lobe and splenium of the corpus callosum.…”
Section: Discussionmentioning
confidence: 99%
“…[20] DTI is a highly sensitive technique for investigating the integrity of WM microstructure and can be very useful in assessing the optic tract integrity by FA measurements. [202122] Correlation between VEP and FA has been already confirmed in patients with neuromyelitis optica and sclerosis multiplex. [2324] Our results show that FA values of inferior left and right OWM were significantly higher in the comparison group compared to the group of children with abnormal VEP.…”
Section: Discussionmentioning
confidence: 98%
“…The well connectivity of the callosal fibers is influenced by alterations of visual input [ 42 ]. Kwinta et al detected low FA values of the CC in premature infants with abnormal stereoscopic vision and visual perception [ 43 ]. Consistent with previous researches, we speculated that the decrease of FA and increase of RD indicated the integrity of inner structure of the CC was damaged and potential pathologic changes or degeneration may occur in the callosal fibers in RVO patients, which may leads to inability to integrate visual information and further cause visual deprivation.…”
Section: Discussionmentioning
confidence: 99%